Adaptation and collaboration of local community in super priority destination tourism program in Labuan Bajo - Islahuddin, Islahuddin; Eppang, Buntu Marannu; Som, Ahmad Puad Mat; Masatip, Anwari; Salim, Muhammad Arfin Muhammad (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
This article is an elaborative description of the adaptive and collaborative forms of local communities in the context of tourism development. The people of Labuan Bajo realize that the environment in which they live for generations has now become the target of the Super Priority Destinations (SPD) program. The research method used is descriptive qualitative research. Data was collected by using in-depth interviews, observations, focus group discussions (FGD) and documentation studies. In Labuan Bajo, the role of the local community is shown through their transformation from a community with the characteristics of fishermen to the tourism industry on a micro basis. The role of local communities must be increased so that they do not only enjoy the crumbs of the big program of Super Priority Destinations (SPD). They are facing a change in economic orientation, where the tourism sector provides new opportunities to improve their welfare. This article strengthens the argument for the importance of collaborating with stakeholders, namely local communities, government, tourism actors (businesses), and academics. The importance of strengthening awareness and more comprehensive local community tourism education can be achieved by encouraging the role of universities. There are at least three stages of strategy that emerged from the results: identification of collaborating stakeholders as a precondition for making commitments, between government, private sector, community, and academia; unit process as a space to determine the right strategy; and unit of results as the alignment of program implementation, consistency of commitment, and the formation of norms in. In this context, universities have a role in producing human resources and conducting research to answer the needs of the tourism industry.